2015
DOI: 10.1186/s13071-015-0803-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of underappreciated vectors in malaria transmission in an endemic region of Bangladesh-India border

Abstract: BackgroundDespite the efforts of the National Malaria Control Programme, malaria remains as an important public health problem in Bangladesh, particularly in the south-eastern region bordering India. Successful malaria control strategies rely on a detailed understanding of the underlying causes of malaria transmission. Here, an entomological survey was conducted in a malaria endemic area of Bangladesh bordering India to investigate the Anopheles mosquito community and assess their Plasmodium infection status.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 23 publications
1
23
0
5
Order By: Relevance
“…Moreover, it has been reported that the K13-propeller mutations in P. falciparum reached high prevalence in Myanmar, next to the northwestern border with India [27]. Such emergence of artemisinin resistance to P. falciparum  strains in neighbouring India and Myanmar could be transmitted through malaria vectors active in remote border areas of Bangladesh [28, 29]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that the K13-propeller mutations in P. falciparum reached high prevalence in Myanmar, next to the northwestern border with India [27]. Such emergence of artemisinin resistance to P. falciparum  strains in neighbouring India and Myanmar could be transmitted through malaria vectors active in remote border areas of Bangladesh [28, 29]. …”
Section: Discussionmentioning
confidence: 99%
“…were found to be responsible for malaria transmission in CHT among those Anopheles jeyporiensis, An. maculatus , Anopheles vagus and Anopheles nivipes might be playing important roles [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, much of the exposure to malaria of these daytime travellers was likely not inside the forest. In this area, as in much of Southeast Asia, many of the malaria vectors that bite during the day are known to be present outdoors near the peripheries of villages, forest fringes and fragmented forest areas [54][55][56]. In addition to protection of forest goers, it is thus important to also protect this group of daytime travellers from infection during their workrelated travel.…”
Section: Discussionmentioning
confidence: 99%